On the Meaning and Use of History in Philosophy of Science - Esposito-Varriale, M (UNIV EL BOSQUE, 2018)
The paper explores some of the meanings and uses of history in the philosophy of science. I argue that the absence (or presence) of history in the philosophical reflections of science does not depend from the lack of discussion between historians and philosophers. Rather, it follows from the clash between two radically different philosophical conceptions of knowledge. On the one hand, we have an "idealist" conception of knowledge, which defends a perspective of reason as autonomous from any contingent and particular element that might orient scientific cogitations. On the other hand, we have a "materialist" conception of knowledge, which is largely inclined towards the situated and contextual conditions making particular forms of knowledge possible. The two traditions have different histories and different understandings of science. The former is generally theory-centred and more focused over the analysis of successful scientific theories in terms of coherence, predictive power and empirical adequacy. The latter, instead, is mostly "praxis" centred and interested on how scientific practices, instruments, interests and goals shape particular forms of knowledge. I also argue that while the "idealist" conception of epistemology is closer to a Naturwissenschaften s outlook; the "materialist" one fits more with a Geisteswissenschaften s approach. Accordingly, while in the former case historical wisdom is auxiliary, in the latter case history is indispensable. I conclude that once we accept such distinction, many of the traditional dichotomies that have haunted philosophy of science so far- i.e. externalism or internalism, discovery or justification - need to be radically reframed.